Cegah Stunting Dengan Tanaman Obat Keluarga: Cegah Stunting Dengan Tanaman Obat Keluarga - Alaydrus, Syafika; Rianto, Rianto; Rusliyana, Rusliyana; Dewi, Niluh Puspita; Anwarudin, Wawang (Jurnal Mandala Pengabdian Masyarakat, 2024)
Indonesia has quite a serious nutritional problem which is characterized by many cases of malnutrition. Malnutrition is an impact of nutritional status. 2016 National Health Service data recorded that the prevalence of stunting reached 33.6%, this is an important health problem because the stunting problem is above the 20% threshold. Meanwhile, stunting in children under five is caused by multifactors, such as nutritional consumption during pregnancy, maternal knowledge about nutrition, limited access to services, inadequate access to sanitation and clean water. This counseling aims to help increase public knowledge, about preventing stunting in toddlers and is a form of the Tri Dharma of Higher Education. Counseling is provided using an interactive lecture method through distributing leaflets, health checks, providing nutritious food, providing TOGA books and social service. The effectiveness of the extension was tested by administering a questionnaire on community satisfaction with the activities carried out. The results of this service activity provide the Sejahtera village community with knowledge about what stunting is, the causes of stunting, the dangers of stunting in the long term and how to overcome the impact of stunting so that stunting can be minimized in children.